Endoscopic Dacryocystorhinostomy Outcomes with Versus Without Adjunctive Mitomycin-C Application - Dr. Vivekkumar Makadiya; Dr.Krishna Makadia, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background Current medical procedures perform endoscopic dacryocystorhinostomy (DCR) as a minimally invasive method for treating nasolacrimal duct obstruction. To enhance success rates, adjunctive therapies such as mitomycin-C (MMC) have been utilized to reduce fibrosis and maintain the patency of the surgically created ostium. However, the clinical efficacy of topical MMC application in endoscopic DCR remains a topic of debate. Methods Medical researchers studied endoscopic DCR surgery among primary patients who had nasolacrimal duct obstruction. Participants were divided into two groups: Group A, which received intraoperative topical MMC (0.2 mg/mL for 5 minutes) applied to the osteotomy site, and Group B, which underwent the same surgical procedure without MMC. Outcome measures included symptomatic relief, ostium patency assessed by irrigation tests and endoscopic examination, and postoperative complications at 3, 6, and 12 months. Results The researchers reviewed 100 patients distributed between two groups with 50 participants each. At 12-month follow-up, Group A demonstrated a higher ostium patency rate compared to Group B (94% vs 86%, respectively). Patients in the MMC group reported fewer instances of partial lacrimal drainage block and granulation tissue formation. Surgical time and immediate postoperative pain were similar in both groups. Complications were minor and included mild hemorrhage and transient nasal mucosal irritation. No major adverse events related to MMC were observed. Conclusion The proportion of successful outcomes in endoscopic DCR improves when medical instruments containing MMC are added to the surgical procedure to minimize ostium blockage from granulation tissue and scar tissue formation. Further large-scale, multicenter trials are warranted to confirm these results and establish standardized protocols for MMC dosage and application duration.